Oxidation of Cylindrospermopsin by Fenton process : a bench-scale study of the effects of dose and ratio of H2O2 and Fe(II) and kinetics - Ferreira, Matheus Almeida (2021)
The cyanotoxin cylindrospermopsin (CYN) has become a significant environmental and human health concern due to its high toxicological potential and widespread distribution. High concentrations of cyanotoxins may be produced during cyanobacterial blooms. Special attention is required when these blooms occur in sources of water intended for human consumption since extracellular cyanotoxins are not effectively removed by conventional water treatments, leading to the need for advanced water treatment technologies such as the Fenton process to produce safe water. Thus, the present study aimed to investigate the application of the Fenton process for the degradation of CYN at bench-scale. The oxidation of CYN was evaluated by Fenton reaction at H2O2/Fe(II) molar ratio in a range of 0.4 to 4.0, with the highest degradation of about 81% at molar ratio of 0.4. Doubling the concentrations of reactants for the optimized H2O2/Fe(II) molar ratio, the CYN degradation efficiency reached 91%. Under the conditions studied, CYN degradation by the Fenton process followed a pseudo-first-order kinetic model with an apparent constant rate ranging from 0.813 × 10−3 to 1.879 × 10−3 s −1 .